The structure of monododecyl pentaethylene glycol monolayers with and without added dodecane at the air/solution interface: A neutron reflection study - Lu, JR; Li, Z; Thomas, R; Binks, B; Crichton, D; Fletcher, P; McNab, JR; Penfold, J (1998)
Neutron reflectometry and surface tensiometry have been used to study the composition and structure of a mixed monolayer of dodecane and the nonionic surfactant pentaethylene glycol monododecyl ether (C12E5) and the structure of the C12E5 on its own at the surface of aqueous solutions of C12E5. Partially labeling of the surfactant with deuterium gave the surface normal distributions of the ethylene glycol and hydrocarbon chains of the surfactant and of the water, and these results are compared with those from other members of the C12Em series. The C12E5 layer has a higher capacity for oil than that of the comparable hydrocarbon chain length cationic surfactant, dodecyl trimethylammonium bromide (C12TAB), and the structure of the composite layer is also different. The separation of the centers of the surfactant chain and dodecane distributions is only 3 Å in the C12E5 system in comparison with 6.5 Å for C12TAB. In this respect, the C12E5/dodecane system more closely resembles the sodium dodecyl sulfate/dodecanol system, and this is attributed to a favorable interaction between the dodecane and the ethylene glycol chain, which encourages a closer approach of the oil to the water surface. The hydrocarbon chain in the C12Em series where m is 6 or less is tilted at about 40° away from the surface normal. Upon incorporation of dodecane into the C12E5 layer, the hydrocarbon chain changes to an almost perpendicular orientation.